Panics and their causes - Westgate, J.M. (My University, 1897)
Introduction: Since panics are diseases of our monetary or circulatory system to understand them we must first observe at least the general structure of the giant mechanisms by which the business of the entire civilized world is carried on. In tracing the evolution of money and that of its offspring—credit, we must begin with the most primitive forms of exchange, namely barter. This is the exchanging of commodity for commodity no medium of exchange being involved. While this first step upward is a great one, yet it has many disadvantages. The following are some of the most evident. 1. Every article of exchange must be given an exchange value in terms of every other commodity on the market. One hundred such articles would, under the barter system require no less than 4950 different ratios of exchange, whereas by the use of a medium of exchange the number of necessary ratios is reduced to one hundred. 2. Most articles cannot be divided without seriously impairing their value. 3. The difficulty which exists of finding a trading group or pair—The man who has the coat I wish may not want the pair of shoes I have to offer.
Citation: Westgate, J.M. Panics and their causes. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Economics; Monetary systems; Trade; Panic; Theses; Manuscripts (documents)